THE EFFECTIVENESS OF PROJECT-BASED LEARNING ON SCIENCE EDUCATION: A META-ANALYSIS SEARCH - Nuri Balemen; Melike Ozer Keskin (Informascope, 2018)
The present study aims to demonstrate, by means of a meta-analysis, the effectiveness of Project-Based Learning in the context of academic performance and various study characteristics. For this purpose, the relevant literature was reviewed to identify studies using Project-Based Learning in the fields of physics, chemistry, biology, and science. Following the literature review, the study characteristics and the criteria for their inclusion were determined. A total of 48 studies were included and, by means of the analyses conducted, the general effect size of Project-Based Learning in science education was found to be 1.063. This is quite a large effect size by Cohen's criteria and it shows that Project-Based Learning is 86% more effective in science education compared to traditional learning approaches. Project-Based Learning was found to have a great effect size in different subjects (physics, chemistry, biology, and science), at different levels (primary, secondary, and tertiary), and with samples of various sizes (small, medium, and large). Project-Based Learning can thus be deemed more effective compared to traditional learning approaches.